GRAMMATICAL COHESION IN BORIS JOHNSON'S SPEECH ENTITLED CORONAVIRUS SPREAD IN UK - Winanda Reisty Oktavia; Suprayogi Suprayogi (Linguistics and Literature Students' Journal, 2021)
This paper analyzes grammatical cohesion in Boris Johnson’s Speech entitled coronavirus spread in UK. This research is aims to find out which types of grammatical cohesion is the most used in the speech. The research method is qualitative research and the researcher used theories from Halliday and Hasan (1976) to analyze the cohesion. Data of this research is the speech video of Boris Johnson posted in BBC news Youtube channel on May 2020. The researcher found that the grammatical cohesion used in Boris Johnson’s speech about coronavirus spread in UK are reference, substitution, ellipsis and conjunction. There are 181 references, 2 substitutions, 2 ellipses and 80 conjunctions. The dominant kinds of cohesion in this speech there is reference with the total 181 and divided into three types: personal reference (122), demonstrative reference (50) and comparative reference (9). The use of cohesion is needed to make those messages is acceptable, a series of sentences, a choice of words must be integrated with each other so that the essence of the message communicated can be conveyed.Keywords: Discourse, grammatical cohesion, speech